TRADITION IN THE POETRY OF ABDULLAH SHER (Scientific journal of the Fergana State University, 2024)
This article talks about the work of poet and translator Abdulla Sher and analyzes the tradition and its types in his work through examples. The creators continued the tradition of genres in our literature, as well as the ideas presented in those works. As the writer reacts to events and incidents in life, he describes them in the same way, and creates such an attitude in the readers towards these events. The artistic and emotional content of the work is revealed by the artistic idea of ​​the work. Therefore, the main idea, like the main theme, consists of the ideas embodied in the characters, their behavior and events, and represents the attitude of the writer to these characters and events, that is, to life. The idea arises in the creative process and is expressed in the concrete material of the work. Accordingly, the ideological and thematic essence of the work is determined by analyzing images and events. In the poems of the poet, the priority of universal values ​​and the need to reflect the reality of life are at the top. Based on his ideas and aspirations, the creator divides various processes, people's activities, things and events into good and bad, useful and harmful, merit and sin, and evaluates them. This means the evaluation function of the artistic outlook based on the poet's philosophy and his attitude to social life.